Creating optimal environments for talent development: An holistic ecological approach - Henriksen, K.; Stambulova, N. (Routledge handbook of talent identification and development in sport, 2017)
The previous sections of the book have introduced two main perspectives on athletic talent. The talent discovery approach is based on the notion that there is an innate reservoir of talent and that systematic assessment and selection of talented athletes results in a more efficient use of resources (Howe, Davidson, & Sloboda, 1998). The talent development approach places more emphasis on the quantity and quality of training that athletes need to reach top-level performance (Cote, Lidor, & Hackfort, 2009; Ericsson, Krampe, & Tesch-Romer, 1993). The holistic ecological approach (HEA) (Henriksen, 2010; Henriksen, Stambulova, & Roessler, 2010a, 2010b, 2011), which is introduced in this chapter, proposes a shift in research attention from the individual athletes to the broader developmental context or environment in which they develop. The HEA integrates the somewhat opposing talent discovery and development approaches by focusing on how an environment manages the balance between these two, and how this balance becomes a part of the environment`s identity. Introduction to the holistic ecological approach to talent development The HEA was developed partly to answer the call for theoretically guided research on ecological approaches to talent development in sport (Araujo & Davids, 2009; Krebs, 2009). The HEA focuses on the whole environment, and suggests that some environments are superior to others in their capacity to guide talented junior athletes in their transition to elite senior athletes. In this section, we introduce key aspects of HEA, including ecologically inferred definitions of athletic talent and talent development, two working models, a definition of the athletic talent development environment (ATDE), and criteria for its success.